ANALISIS STRATEGI PENGEMBANGAN USAHA TERNAK AYAM BROILER DI CV RIZKI JAYA - Kurniawan, Rizki Andika (Jurnal Riset Entrepreneurship, 2019)
The purpose of this study is to find out how the marketing management strategy with the SWOT analysis method can be able to develop business on CV. RIZKI JAYA and the most appropriate S-O strategy used to support increased turnover at CV RIZKI JAYA. Based on the results of the study obtained from the results of the SWOT analysis of the strength score (strenght) 2.68, weakness (weakness) 0.33, opportunity (2.52), and threat (threat) 0.37. From the SWOT diagram can be seen from the difference in the score of strengths and weaknesses, the value of the higher strength score with the difference of 2.35. While the value of opportunity and threat scores is higher opportunities with a difference of 2.15. So that clearly shows that CV. RIZKI JAYA has been on the right track, therefore to support a proven turnover increase that the company's current position in quadrant 1 is a very favorable situation by continuing to carry out aggressive strategies to expand its business and increase turnover. Where the general strategy that can be used by companies is to use the power of the company to take every advantage on the opportunity, which is to improve an effective and efficient management system by establishing good relationships with consumers and other entrepreneurs to make marketing easier for the company, improve meat quality good, and increase HR to be trusted by consumers by participating in training related to chicken farming.